Long-range spin chirality dimer order in the Heisenberg chain with modulated Dzyaloshinskii-Moriya interactions - Avalishvili, N. (2019)
The ground-state phase diagram of a spin S = 1 2 XXZ Heisenberg chain with spatially modulated Dzyaloshinskii-Moriya interaction H= n{J(Sx nSx n+1 +Sy nSy n+1 )+JzSz nSz n+1 +[D0 +(−1)nD1](Sx nSy n+1 −S y nSx n+1 )}is studied using the continuum-limit bosonization approach and extensive density-matrix renormalizationgroupcomputations.Itisshownthattheeffectivecontinuum-limitbosonizedtheoryofthemodelisgivenby the double-frequency sine-Gordon model (DSG) where the frequencies, i.e., the scaling dimensions of the two competing cosine perturbation terms, depend on the effective anisotropy parameter γ∗ =Jz/ J2 +D2 0 +D2 1. Exploring the ground-state properties of the DSG model we show that the zero-temperature phase diagram contains the following four phases: (i) the ferromagnetic phase at γ∗ −1; (ii) the gapless Luttinger-liquid (LL) phase at−1 <γ∗ <γ∗ C1 =− 1/√2; (iii) the gapped composite (C1) phase characterized by coexistence of the long-range-ordered (LRO) dimerization pattern ∼ (−1)n(SnSn+1) with the LRO alternating spin chirality pattern κ ∼ (−1)n(Sx nSy n+1 −Sy nSx n+1 ) atγ∗ C1 <γ∗ <γ∗ C2; and (iv) at γ∗ >γ∗ C2 > 1 the gapped composite (C2) phase characterized in addition to the coexisting spin dimerization and alternating chirality patterns, by the presence of LRO antiferromagnetic order. The transition from the LL to the C1 phase at γ∗ C1 belongs to the Berezinskii-Kosterlitz-Thouless universality class, while the transition at γ∗ = γ∗ C2 from C1 to C2 phase is of the Ising type.